Effect of Atmospheric Corrosion on the Mechanical Properties of SAE 1020 Structural Steel - Carola Martínez; Francisco Briones; María Villarroel; Rosa Vera (Materials, 2018)
Resistance to atmospheric corrosion in different environments located in Chile and the corrosion’s effect on the mechanical properties of SAE 1020 steel were studied. Atmospheric corrosivity categories at each station under study were determined. These categories were C2, for Laja; C3 and C4, for the Arica and Antarctic stations, respectively; and the most aggressive, C5 and higher at Quintero. These specific environments significantly influenced the mechanical responses of steel exposed for 36 months. Rupture elongation, the modulus of toughness, ultimate tensile strength, and hardness of the material all decreased as a function of environmental atmospheric aggressiveness. Lowered ductility is the result of the increased corrosion rate due to the high deposition of chlorides. This is due to the morphology of material degradation, which consequently occurs as pores, microstrains, and other defects that promote early rupture of the steel.